Pelatihan Penanaman Mangrove di Desa Eyat Mayang Kabupaten Lombok Barat dalam Upaya Mencegah Abrasi Pantai - Dharmawibawa, Iwan Doddy; Royani, Ida; Imran, Ali (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
Coastal areas and beaches are areas that are widely used by the community to carry out various activities, such as: fishing, aquaculture, tourism, transportation and other activities. Various kinds of activities in coastal areas cause the carrying capacity of the environment to decrease. One form of ecosystem that plays an important role in coastal areas is the mangrove ecosystem. The aim of this service activity is to practice mangrove planting in Eyat Mayang Village, Sheet District, West Lombok Regency in an effort to prevent coastal erosion. This training activity was carried out in three stages, namely: preparation, implementation and evaluation. The results of this service activity, namely the practice of seeding, planting mangroves, and maintaining mangroves have been carried out well. The community is very enthusiastic about the activities of breeding mangrove seeds and maintaining mangrove forests, because they can feel the benefits of the existence of mangrove forests in protecting coastal ecosystems.